Incorporation of sporopollenin enhances acid–base durability, hydrophobicity, and mechanical, antifungal and antioxidant properties of chitosan films - Kaya, Murat; Akyüz, Lalehan; Sargın, İdris; Mujtaba, Muhammad; Salaberria, Asier M.; Labidi, Jalel; Çakmak, Yavuz S.; Koç, Behlül; Baran, Talat; Çeter, Talip (Elsevier BV, 2017)
Sporopollenin-chitosan blend films were produced for the first time. Sporopollenin is a robust structural component of plant pollens exhibiting excellent features such as nontoxicity, biodegradability, biocompatibility, high thermal stability, durability to strong acid and base solutions and homogeneity in size. To benefit from these advantages, sporopollenin samples obtained from Betula pendula (silver birch) were incorporated into chitosan film at different concentration; 10, 20 and 40 mg in 100 mL chitosan gel (1%). Stereo microscopy, FT-IR and TG/DTG analyses showed that sporopollenin was successfully incorporated into the chitosan matrix. Incorporation of sporopollenin in gradually increasing amount into chitosan films was found advantageous in (1) enhancement in chemical durability of the films, (2) increment of hydrophobicity, (3) boosting the mechanical properties, (4) improvement of antifungal and (5) antioxidant activities. This study revealed that sporopollenin can be suggested as an effective blend material for biodegradable edible chitosan film production.
Keywords: Bioplastic; Edible film; Betula pendula; Biodegradable; Pollen; Betula Pendula